THE ROLE OF RIOCIGUAT IN THE TREATMENT OF PULMONARY ARTERIAL HYPERTENSION ASSOCIATED WITH CONNECTIVE TISSUE DISEASE - O. Ya. Vasiltseva; K. I. Ivanov; E. A. Devetyarova; O. E. Yakovleva (Евразийский Кардиологический Журнал, 2019)
Soluble guanylate cyclase (sGC) is a key signal-transduction enzyme activated by nitric oxide (NO). Binding NO with sGC - enzyme catalyzes the synthesis of a signal molecule of cyclic guanosine monophosphate (cGMP), which plays an important role in the regulation of processes that affect vascular tone, proliferation, fibrosis and inflammation. Impaired bioavailability and/or responsiveness to endogenous NO has been implicated in the pathogenesis of cardiovascular and other diseases. Pulmonary arterial hypertension (PAH) is a well-known complication of systemic connective tissue diseases (CTD) and ranks second among the most common types of PAH after idiopathic PAH (IPAH). The usage of organic nitrates and other NO donors has limitations, including non-specific interactions of NO with various biomolecules, lack of response and the development of tolerance following prolonged administration. Compounds that activate sGC in NO-independent manner might therefore provide considerable therapeutic advantages. The purpose of this article is to provide contemporary data on the management and treatment of patients, as well as the role of specific therapy and the place of riociguat in the treatment of patients with CTD associated PAH